2020
DOI: 10.1002/bjs.11469
|View full text |Cite
|
Sign up to set email alerts
|

Biological subtype, treatment response and outcomes in inflammatory breast cancer using data from the National Cancer Database

Abstract: Background Although inflammatory breast cancer (IBC) is postulated to be a distinct biological entity, practice guidelines and previous data suggest that treatment and outcomes are influenced by standard approximated biological subtype. The aim of this study was validation in a large recent National Cancer Database (NCDB) patient cohort. Methods Patients with non‐metastatic IBC treated in 2010–2015 with neoadjuvant systemic therapy and surgery were identified from the NCDB. Approximated biological subtypes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…subtype have been associated with pathologic node negativity, which is predictive of OS 28 after neoadjuvant systemic therapy, approximately only 20% of patients achieve pCR in the breast and axilla. 29 Furthermore, risk stratification methods such as sentinel node biopsy technique have prohibitively high failure rates in IBC patients. Therefore, identification of patients who achieve pCR is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…subtype have been associated with pathologic node negativity, which is predictive of OS 28 after neoadjuvant systemic therapy, approximately only 20% of patients achieve pCR in the breast and axilla. 29 Furthermore, risk stratification methods such as sentinel node biopsy technique have prohibitively high failure rates in IBC patients. Therefore, identification of patients who achieve pCR is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients with non-metastatic IBC treated with neoadjuvant chemotherapy and surgery, identified from the National Cancer Database, the pathological complete response (pCR) rate was 19.1% in those with TNBC. Furthermore, such patients had a worse 5-year survival rate (44%) than those with other subtypes ( 4 ). In our case, a skin biopsy showed that both breast cancers were triple-negative; the tumors were successfully treated with induction dose-dense chemotherapy and bilateral total mastectomy, and pCR was nearly achieved.…”
Section: Discussionmentioning
confidence: 96%
“…A previous study conducted using the SEER database showed that patients with IBC had a poorer overall survival and breast cancer-specific survival rates than those with non-IBC ( 3 ). IBC is more often observed in patients with HER2-positive breast cancer and triple-negative breast cancer (TNBC) than non-IBC ( 3 , 4 ). Among patients with non-metastatic IBC treated with neoadjuvant chemotherapy and surgery, identified from the National Cancer Database, the pathological complete response (pCR) rate was 19.1% in those with TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…The current standard treatment for stage III IBC consists of tri-modality therapy, which includes neoadjuvant systemic therapy followed by modified radical mastectomy (MRM) and post-mastectomy radiation therapy 9 . The use of tri-modality therapy has been associated with 5-year OS rates ranging from 44% in patients with triple-negative IBC to 74% in patients with HER2 + IBC 10 . The incorporation of HER2-directed agents into tri-modality therapy has significantly improved survival outcomes for patients with HER2 + IBC 11 .…”
Section: Introductionmentioning
confidence: 99%